Empowering The Saptawening Coffee Community Bawang Village, Blado District, Batang Regency - Aenurofik Aenurofik; Ade Gunawan (Islamic Studies Journal for Social Transformation, 2018)
Abundant potential in a village should be developed and managed by the local community to fulfill household needs. Bawang Village, Blado Subdistrict, Batang Regency with an altitude of 625-1125 meters above sea level which is a fertile mountainous and hilly area and high rainfall. The natural potential possessed by Bawang Village such as nature tourism is curug (waterfall), hot spring and beautiful scenery. Other potentials such as agriculture, clove and coffee plantations, culinary and culture can be an income for the village community if developed and managed properly. Community awareness in developing potential starts from the community formed by village youths called the coffee community with the name Sapta Wening. The Sapta Wening community begins with learning about coffee management from the grower, care, harvest, post-harvest process to brewing. Learning is carried out by the Sapta Wening community with various methods such as bringing experts to visits to several coffee communities and coffee shops.